Hubungan Perilaku Dengan Gejala Keracunan Pestisida Pada Petani Penyemprot di PT. Anam Koto Pasaman Barat Tahun 2022 - Gusti, Awalia; Yolla, Putri; Nur, Erdi; Zicof, Erik; Wijayantono, Wijayantono (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Padang, 2023)
Behavior (Knowledge, attitude, and action) in spraying pesticides affects the occurrence of poisoning symptoms in farmers spraying pesticides at PT. Anam Koto Pasaman Barat 2022, because pesticide spraying was found with a leaky tank, pesticide spraying farmers did not wear complete PPE (Personal Protective Equipment), male spray farmers smoked immediately with unclean hands, spraying also took place during the hot sun around 12.30 - 13.30. This study aims to determine the relationship between behavior and symptoms of pesticide poisoning in spraying farmers at PT. Anam Koto Pasaman Barat in 2022.This research is a quantitative research with a cross sectional approach conducted at PT. Anam Koto Pasaman Barat 2022 on 17–29 January 2022. The population in this study were pesticide spraying farmers at PT. Anam Koto Pasaman Barat as many as 83 people, with a sample of 45 people. Data was collected through interviews using a questionnaire. Data analysis was univariate and bivariate using Chi-Square statistical test.The results showed that there was a relationship between knowledge (p = 0,045), action (p = 0,004), behavior (p = 0,014) and there was no relationship between attitudes (p = 0,199) with symptoms of pesticide poisoning.The conclusion of this study is that there is a relationship between behavior and symptoms of poisoning in pesticide spraying farmers at PT. Anam Koto Pasaman Barat 2022.To reduce the symptoms of poisoning in farmers spraying pesticides. Pesticide sprayers should turn bad actions into correct actions in handling pesticides and the need for cooperation between the agriculture office and the health office in monitoring and assisting the use of pesticides by farmers.